INFLUENCE OF INTEGRATED USE OF POULTRY MANURE ALONG WITH MINERAL FERTILIZER ON SOIL PROPERTIES, GROWTH TRAITS, AND WHEAT YIELD - Katyar, N. K.; Rais, N.; Rajput, A.; Qureshi, S. A.; Deho, N. A. (Pak. J. Agri. Engg., Vet. Sci., 2024)
Soil quality and health, in the environment of agrarian ecosystems, pose significant enterprises due to environmental decline and overreliance on chemical inputs. To address this challenge, there is a pressing need to borrow and incorporate an approach that combines both organic and inorganic sources of plant enriched. In pursuit of this objective, a field trial was led in rabi season 2023 to evaluate the synergistic effect of organic and mineral nutrient sources on soil characteristics and the growth and yield of wheat crops. The experimental design featured four distinct treatments planned in a randomized complete block design (RCBD), each with four replicates. These treatments involved the application of poultry manure at varying rates: T1 0 ton ha-1, T2 4 ton ha-1, T3 6 ton ha-1, and T4 8 ton ha-1. The chosen wheat variety for cultivation was Benazir. Notably, the treatment involving the application of 650 kg ha-1 of poultry manure alongside half of the recommended dose of inorganic fertilizer (Treatment 4) yielded the most promising results. This treatment yielded a wheat crop with a maximum plant height of 73 cm, an average of 14 tillers per plant, a spike length of 12.51 cm, and an impressive grain yield of 3268 kg ha-1. The grain yield was increased by 11.4% over the control treatment. Consequently, this study's findings suggest that farmers may benefit from adopting the practice of applying 650 kg ha-1 of poultry manure in combination with half of the recommended quantity of chemical fertilizer. Such an approach not only reduces the reliance on chemical fertilizers but also enhances soil quality and overall soil health. Soil organic matter was enhanced by 24% at the dose of treatment 4. Additionally, it contributes to lowering production costs and improving the livelihoods of small-scale farmers.